2011
DOI: 10.1111/j.1476-4431.2011.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiac output measurement in dogs by transpulmonary pulse contour analysis

Abstract: Compared with lithium dilution, the pulse contour analysis provides a good estimation of CO, but requires femoral artery catheterization in anesthetized dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 31 publications
0
41
1
1
Order By: Relevance
“…A limitation of the TPTD CO method is the requirement for catheterization of a central artery. More peripheral arteries (eg, dorsal metatarsal artery in dogs) would be more practical and carry lower risk of complications, but in one report the TPTD CO monitor failed to detect a 20 mL bolus of ice‐cold physiological saline when a 22 cm long thermodilution catheter was placed in the dorsal metatarsal artery in 8 out of 30 attempts for calibrating the PCA CO with TPTD CO . Although no catheter‐related complications were observed in the present report, femoral artery catheterization might result in increased risk of bleeding/hematoma and these potential morbidities should be considered if the technique is used in veterinary patients.…”
Section: Discussioncontrasting
confidence: 51%
“…A limitation of the TPTD CO method is the requirement for catheterization of a central artery. More peripheral arteries (eg, dorsal metatarsal artery in dogs) would be more practical and carry lower risk of complications, but in one report the TPTD CO monitor failed to detect a 20 mL bolus of ice‐cold physiological saline when a 22 cm long thermodilution catheter was placed in the dorsal metatarsal artery in 8 out of 30 attempts for calibrating the PCA CO with TPTD CO . Although no catheter‐related complications were observed in the present report, femoral artery catheterization might result in increased risk of bleeding/hematoma and these potential morbidities should be considered if the technique is used in veterinary patients.…”
Section: Discussioncontrasting
confidence: 51%
“…Invasive CO monitoring during surgery is infrequently performed in dogs using the pulmonary artery catheter [3] due to many factors, including associated complications such as arrhythmias, thromboembolism or pulmonary artery rupture [5], the availability of equipment and costs. The high incidence of cardiac arrhythmia observed in the present study indicates that the risk-benefit ratio of the right cardiac catheterisation should be considered according to the haemodynamic status of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The TD technique can be relatively imprecise when measuring CO due to factors that can influence the accuracy of the measurement, such as dead space of the catheter, velocity of the administration and temperature of the solution [2]. However, this is still considered the gold standard for CO determination [3]. Despite the results of the present study having demonstrated that the TEE is an alternative technique to TD for measuring CO, in some situations, such as in surgeries of the oral, oesophageal or gastric areas, this technique cannot be applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other non‐invasive methods that have not been considered suitable for CO monitoring in dogs include arterial pulse contour analysis (Bektas et al ), arterial pressure waveform analysis (Cooper & Muir ), transthoracic bioimpedance and the partial CO 2 rebreathing methods (Yamashita et al ), although the latter was only considered reliable for large breed dogs (Haryadi et al ). Of the suitable methods, only transpulmonary pulse contour analysis provides continuous monitoring, although it requires femoral artery catheterisation (Shih et al ). Therefore, the development of other reliable methods for continuous CO monitoring in dogs is necessary.…”
Section: Introductionmentioning
confidence: 99%